Development, characterisation and in vitro evaluation of lanthanide-based FPR2/ALX-targeted imaging probes. Issue 44 (1st November 2019) - Boltersdorf, Tamara; Ansari, Junaid; Senchenkova, Elena Y.; Jiang, Lijun; White, Andrew J. P.; Coogan, Michael; Gavins, Felicity N. E.; Long, Nicholas J.
Abstract : Formyl Peptide Receptor (FPR)-targeted lanthanide complexes with long-lived emission in stimulated human neutrophils. Abstract : We report the design, preparation and characterisation of three small-molecule, Formyl Peptide Receptor (FPR)-targeted lanthanide complexes (Tb·14, Eu·14 and Gd·14 ). Long-lived, metal-based emission was observed from the terbium complex ( τ H2 O = 1.9 ms), whereas only negligible lanthanide signals were detected in the europium analogue. Ligand-centred emission was investigated using Gd·14 at room temperature and 77 K, leading to the postulation that metal emission may be sensitised via a ligand-based charge transfer state of the targeting Quin C1 unit. Comparatively high longitudinal relaxivity values ( r 1 ) for octadentate metal complexes of Gd·14 were determined (6.9 mM −1 s −1 at 400 MHz and 294 K), which could be a result of a relative increase in twisted square antiprism (TSAP) isomer prevalence compared to typical DOTA constructs (as evidenced by NMR spectroscopy). In vitro validation of concentration responses of Tb·14 via three key neutrophil functional assays demonstrated that the inflammatory responses of neutrophils ( i.e. chemotaxis, transmigration and granular release) remained unchanged in the presence of specific concentrations of the compound. Using a time-resolved microscopy set-up we were able to observe binding of the Tb·14 probe to stimulated human neutrophils around the cell periphery, while in the same experiment with un-activated neutrophils, no metal-based signals were detected. Our results demonstrate the utility of Tb·14 for time-resolved microscopy with lifetimes several orders of magnitude longer than autofluorescent signals and a preferential uptake in stimulated neutrophils.